Criminal Courts in England and the United States: A comparative approach to fictional representations as portrayed by two classic examples of courtroom films: Witness for the Prosecution (1957) and Anatomy of a Murder (1959) - Anne-Laure Dubrac (Angles)
The objective of this paper is to analyse and compare representations of the legal systems of England and the United States in two courtroom films: Witness for the Prosecution (1957) by Billy Wilder and Anatomy of a Murder (1959) by Otto Preminger. After a brief analysis of the links between law and fiction, the article presents an overview of how these films represent the professional environments that are central to their stories. It then explores differences and similarites between English and American law in theory and in practice. Since this article is addressed to French law students, it also makes occassional reference to the Civil Law system and to the inquisitorial procedure.